Prognostic Values of Systemic Inflammation Response (SIR) Parameters in Resectable Cervical Cancer - Wen-Jie Wang; Ying Li; Jie Zhu; Min-jie Gao; Jian-ping Shi; Yue-qing Huang (SAGE Publishing, 2019)
Background: Cervical carcinoma is the leading cause of cancer mortality in women. C-reactive protein (CRP), albumin (ALB), globulin (GLB), lactate dehydrogenase (LDH), and albumin-to-globulin ratio (AGR) are indicators of systemic inflammation response correlated with tumor outcomes. Methods: This study recruited 110 patients with cervical cancer. The patients were divided into 2 groups according to pretreatment median values of CRP, ALB, GLB, LDH, and AGR. The post/preradiotherapy or post/pretreatment ratios were defined as rates of pretreatment CRP, ALB, GLB, LDH, and AGR values and the corresponding ones obtained after radiotherapy or whole treatment. Results: Higher pretreatment CRP or LDH levels were correlated with worse progression-free survival (PFS) and overall survival (OS). Increased post/preradiotherapy CRP ratio was correlated with worse PFS and OS, increased post/preradiotherapy LDH ratio was correlated with worse PFS. Increased post/pretreatment CRP ratio was correlated with worse PFS and OS, not-increased post/pretreatment AGR ratio was correlated with worse OS. Cox regression analysis model indicated that, moderately or poorly of differentiation, higher pretreatment CRP or LDH levels were independently associated with worse PFS, higher pretreatment CRP or LDH levels and increased post/pretreatment CRP ratio were independently associated with worse OS. Conclusion: CRP, LDH, or AGR are correlated with outcomes of resectable cervical cancer.